Using scenarios to understand community-based interventions for bushmeat hunting and consumption in African savannas. (August 2020) - van Velden, Julia L.; Travers, Henry; Moyo, Boyson H.Z.; Biggs, Duan
Abstract: Community-based interventions are an important strategy to reduce bushmeat hunting, one of the key threats to African wildlife. However, understanding the possible effects of such programs prior to implementation is vital, in order to ensure that scarce funds are correctly directed. Here we used scenario-based interviews to explore the potential effects of seven programs on proxies for bushmeat hunting and consumption, including the provision of alternative protein sources, the provision of alternative incomes, and the harvesting of natural resources from protected areas. We conducted 250 interviews with respondents living around four protected areas in Malawi, and investigated how time budgets, household and village meat availability, and perceptions of fairness would change under each program. Respondents were most likely to substitute their current activities (including illegal hunting) under alternative income projects such as microenterprise and skills-training programs. All programs except increased enforcement were likely to increase the availability of meat in both households and villages. However, the effect of the scenarios on meat availability was perceived to be greater at village level than household level. Projects that provided long-term benefits such as a microenterprise program or skills training, were preferred over, and seen to be fairer than, programs relating to resource use, such as regulated hunting or park-based resource harvesting schemes. These results illustrate that programs that can harness development goals, while linking back to conservation rules, may successfully reduce bushmeat hunting and consumption around protected areas.